ANALISA PRESSURE BUILD UP TEST MENGGUNAKAN SOFTWARE ECRIN DAN METODE MANUAL PADA SUMUR GAS CP-52 & CP-54 LAPANGAN CHAPIN - Adven Charlos M Pappin; Trijana Kartoatmodjo; Pauhesti Rusdi (President University, 2017)
The CP-52 and CP-54 wells are located on the Tambun structure of Bekasi Regency of West Java Province with the target formation being Baturaja. The pressure build up analysis is carried out for monitoring activities to obtain reservoir and boundary, innitial pressure (Pi), permeability (k), skin (s), ΔP skin, average pressure (Pavg), and flow efficiency information. Tests performed on both wells are pressure build up test (PBU) and to analyze the method of Horner approach pseudo pressure and P2 either manually or with the help of software v.ex.2 v2.02 as validation.